Rudaki: The Genius Preacher - reza mostafavi (Matn/Pizhūhī-i Adabī, 2009)
Some eminent researchers of Rudaki’s works have entitled him “Akfeh,” that is a person who is born blind. The writer of this research study intends to imply that there is clear-cut evidence about knowing him as one of the wisest scholars of the world though he was innately blind. His sagacity and ingenuity impressed the rulers of Samani’s government immensely, so that they made an impassioned plea for help and asked Rudaki to persuade the governor of Bokhara to rethink and get back to Bokhara. He brilliantly succeeded in it. In the second part of this study, the researcher would like to fully discuss and scrutinize the central tenets of Rudaki’s cultivated pieces of advice and delve into his beliefs. As a result, the researcher would come to the point that how the father of Persian poetry can sincerely and professionally share the experiences of his personal life with his readers as he has passed on a lot of constructive and valuable advice_ an ever-lasting memory of his notions and outlook.